Pengaruh Bimbingan Kelompok Teknik Sosiodrama Untuk Meningkatkan Self-Confidence Siswa - Afifah, Aini Nur; Navion, Febranti Putri (Borobudur Counseling Review, 2021)
This study aims to increase self-confidence in students. This study used amethod pre-experimentalof the type of one group pre-test-post-test. The results showed that the provision treatment of sociodrama technique group guidancecan increase self-confidence students', this can be seen through thescores pre-test and post-test. the results of the questionnaire distribution showed an average pre-test score of 79 and an average post-test score of 157. The results of the questionnaire showed an increase in the pretest and posttest self-confidence scores of 78